Adoption and correlates of Postgraduate Hospital Educational Environment Measure (PHEEM) in the evaluation of learning environments – A systematic review*. (1st December 2016) - Chan, Christopher Yi Wen; Sum, Min Yi; Lim, Wee Shiong; Chew, Nicholas Wuen Ming; Samarasekera, Dujeepa D.; Sim, Kang
Abstract: Background: The Postgraduate Hospital Educational Environment Measure (PHEEM) is a highly reliable and valid instrument to measure the educational environment during post graduate medical training. This review extends earlier reports by evaluating the extant adoption of PHEEM in various international clinical training sites, and its significant correlations in order to expand our understanding on the use of PHEEM and facilitate future applications and research. Method: A systematic literature review was conducted on all articles between 2005 and October 2015 that adopted and reported data using the PHEEM. Results: Overall 30 studies were included, encompassing data from 14 countries internationally. Notable differences in the PHEEM scores were found between different levels of training, disciplines, and clinical training sites. Common strengths and weaknesses in learning environments were observed and there were significant correlations between PHEEM scores and In-Training Exam (ITE) performance (positive correlation) and level of burnout (negative correlation), respectively. Conclusions: PHEEM is widely adopted in different learning settings, and is a useful tool to identify the strengths and weaknesses of an educational environment. Future research can examine other correlates of PHEEM and longitudinal changes in interventional studies.